2020
DOI: 10.3389/fonc.2020.596937
|View full text |Cite
|
Sign up to set email alerts
|

Complex ALK Fusions Are Associated With Better Prognosis in Advanced Non-Small Cell Lung Cancer

Abstract: BackgroundEchinoderm microtubule-associated protein-like 4 (EML4) is the canonical anaplastic lymphoma kinase (ALK) fusion partner in non-small cell lung cancer (NSCLC), and ALK-positive patients showed promising responses to ALK tyrosine kinase inhibitors (TKIs). However, studies that comprehensively investigate ALK TKI treatment in patients with different ALK fusion patterns are still lacking.MethodsNinety-eight ALK-positive patients with advanced NSCLC were retrospectively studied for their response to criz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…According to the characteristics of ALK fusion, one reasonable explanation is that different variations at the N-terminus of the ALK fusions affects its subcellular localization and the properties of resulting protein, such as stability and activity, and then further leads to the impact of ALK TKIs on downstream signaling. It has also been demonstrated that patients harboring complex ALK fusions (coexisting canonical and non-canonical ALK fusions) are associated with better treatment outcomes in ALK TKI therapy ( 20 ). For clinicians, to better serve clinical decision-making, it is vital to determine the mutational status of the ALK kinase domain, as well as the therapeutic implications of the partner involved in the fusion.…”
Section: Discussionmentioning
confidence: 99%
“…According to the characteristics of ALK fusion, one reasonable explanation is that different variations at the N-terminus of the ALK fusions affects its subcellular localization and the properties of resulting protein, such as stability and activity, and then further leads to the impact of ALK TKIs on downstream signaling. It has also been demonstrated that patients harboring complex ALK fusions (coexisting canonical and non-canonical ALK fusions) are associated with better treatment outcomes in ALK TKI therapy ( 20 ). For clinicians, to better serve clinical decision-making, it is vital to determine the mutational status of the ALK kinase domain, as well as the therapeutic implications of the partner involved in the fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The response of TKI treatments for ALK-rearrangement patients largely depends on whether the ALK domain is expressed entirely and at high levels driven by the rearranged-partner genes, which are influenced by complex rearrangement structures and RNA splicing mechanisms, and sometimes disaccord on DNA levels and RNA levels. 9 Therefore, RT-PCR and Sanger sequencing were performed to validate the transcription pattern of the fusion gene and confirm the sequences around the breaking point. Notably, the RT-PCR sequencing demonstrated a different type of ALK fusion transcript (ie BCL11A exon 3-ALK exon 20 fusion) in this patient ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 14–16 Notably, some coexistent gene mutations, such as TP53 mutations, also impair the efficacy of ALK-TKI treatment. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LUAD is a pathological type of lung malignancy and can be further divided into different therapeutic subtypes and prognostic subtypes according to the status of multiple genes. For instance, LUAD patients with EGFR mutations and ALK fusion mutations have better treatment options available and higher survival rates than patients without these mutations [27][28][29][30] . Moreover, as immunotherapies have been developed, researchers have found that only some patients with LUAD bene t from these treatments 31 .…”
Section: Discussionmentioning
confidence: 99%